INTEGRASI KEILMUAN DALAM PANDANGAN SYECH AHMAD CHATIB AL MINANGKABAWI - Widia Fithri (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2019)
One of the ulamas of the Nusantara whose influence is so wide to date is Syech Ahmad Chatib Al-Minangkabawi. A very broad influence can be seen from the widespread dissemination of ideas and knowledge into the Islamic world, especially in the archipelago (Indonesia, Malaysia, Brunei, the Philippines and other Malay seas) Koto Tuo born scholars of Gurah IV Angkek Agam West Sumatra, besides having expertise in Fiqh religious fields and others also have expertise in science including mathematics. This paper will examine how the relationship between mathematics and other sciences such as the science of religion, culture, philosophy in the view of Sheikh Ahmad Khatib. this article is important as a hidden heritage of Islamic scholarship that is not much revealed to the surface so that this can be used as a reference, a guideline in the development of scientific integration that is being encouraged in the Islamic world, especially in Indonesia. in Syech Ahmad Chatib's own words it is not known as an integration vocabulary, but this paper will explain how the practice of connection between various sciences in Syech Ahmad Chatib's view. the idea of scientific integration emerged and was voiced today considering the specialization of each of the sciences which is feared to create partial and superficial understanding.